Basic Electrochemistry for Biotechnology - Harnisch, Falk; Sleutels, Tom; Ter Heijne, Annemiek (John Wiley & Sons, 2024)
An advanced textbook that details the fundamental aspects of electrochemistry and bioelectroanalytical methods with a focus on microbial electrochemical technologies. It contains practical experiments and gives answers to specific problems, for an easy entry into the field.